Influencing Factors of Online Impulsive Buying Behavior to Gamers in Purchasing Gaming Peripherals - Fajardo, Michael Dominic; Evangelista, Andrei Joshua; Lambengco, Joey Andrea; Vallesteros, Kayla Marie; Etrata, Antonio (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2024)
The factors that drive gamers' impulsive online behavior in buying gaming peripherals remain poorly understood, despite the Philippines' growing gaming population. This research primarily aims to identify how factors such as self-gratification, novelty, visual attraction, cost saving, reference groups, online shopping convenience, and diversified product selection influence gamers impulsive buying in purchasing gaming peripherals. Descriptive-correlational research design was utilized to analyze the data from 385 respondents. Additionally, descriptive statistics and Multiple Regression Analysis were used to analyze the gathered data and test the relationship of the independent and dependent variable. This study has discovered that 4 of the 7 characteristics significantly affect gamers' impulsive purchasing habits when it comes to gaming peripherals.The results of this study will be useful specifically to gaming peripheral online stores, marketing managers, and product developers to investigate other factors that influence gamers' impulsive buying